Didactic Transposition Analysis on Line and Angle Concepts - Damayanti, Elvina; Ramadianti, Winda; Jumri, Rahmat (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Mathematics knowledge in schools should be sourced from scholarly knowledge. Education not sourced from scholarly knowledge will risk errors in concepts, such as invalidly taught material, that can lead to misconceptions. This study aims to analyze the transposition of knowledge on the concept of lines and angles from scholarly knowledge to knowledge to be taught. This study uses a qualitative descriptive approach. The data source in this study, namely scholarly knowledge, was obtained by analyzing books in universities, while knowledge to be taught was obtained by analyzing mathematics textbooks used in schools. This study's results show a transposition process in the concept of lines and angles, namely in the definition of lines, the types of lines, the position of two lines, and the relationship of angles in two parallel lines. This research can later be the basis for improving mathematical knowledge so that student's understanding of the concept of lines and angles is expected to be more complete based on scholarly knowledge.